Comparative study of immune responses against Clostridium perfringens beta and epsilon toxoids in domestic and laboratory animals using neutralization test - HUQUE, A K M; RAHMAN, M S; LEE, J H (The Indian Journal of Animal Sciences, 2014)
The immune responses against the Clostridium peffringens beta and epsilon toxoids were investigated comparatively in domestic and laboratory animals using the neutralization test. Apparently healthy 12 animals each of cattle, butfalos, sheep, goats, rabbits and guinea pigs were subcutaneously inoculated with the beta and epsilon toxoids. The blood was collected at days 0, 14,21 for sera, and the neutralization tests were performed with the sera. Single dose with the beta and epsilon toxoids induced the immune responses in the animals on days 14 and 21 post inoculation, and there were no adverse reactions after the injection in any of the animals. Statistically significant (P<0.0 1) rise of neutralizing antibody titre production from the 14th day to 21st day post inoculation of toxoids was observed. The highest toxoid neutralizing antibody titre was produced in the sheep. Similar titres were observed between rabbits and cattle, and between guineapigs and buffalos. The neutralizing antibody titres did not vary significantly due to interaction between day of inoculation and toxoid used. It was evident that the Clostridium perfringens betaÂ· and epsilon toxoids produced the maximum immune response in sheep and the implementation of mouse neutralization test provided the rapid and sensitive results making it the procedure of choice for determining the immune responses of clostridial toxoids in the domestic and laboratory animals.